Simulation the spectral dependence of the transmittance for semiconductor thin films - Il'chuk, H.; Kashuba, A.; Petrus, R.; Semkiv, I.; Ukrainets, N. (Physics and Chemistry of Solid State, 2020)
The spectral dependence of the transmittance as a function of the film thickness, the refractive index of the substrate, bandgap and the Cauchy parameters (α and β) of the semiconductor material was determined from condition of interference extremes. The absorption coefficient was simulated for the structure – thin film/substrate. Cadmium chalcogenides (CdTe, CdSe, and CdS) deposited on quartz substrates was selected as model samples. Experimental behavior of substrate transmittance was used to determine its refractive index. The theoretical results are compared with the experimental data and shows good agreement.